Definição de nova referência para localização do seio sigmoideo e do nervo facial nos acessos suboccipitais e suas extensões - Jair Leopoldo Raso (2009)
The suboccipital craniotomy is one of the most commonly performed neurosurgical approaches to the posterior fossa. Surface landmarks help the surgeon to identify and avoid damage to vascular and neural structures related to this approach, as the sigmoid sinus and facial nerve. We have defined a new cranial landmark, the digastric point, and we studied the relationships of this point with others surface landmarks, like the asterion, jugular point, stylomastoid foramen, jugular foramenand sigmoid sinus sulcus. Craniometric measurements were made in 127 dry human adult skulls, 90 male and 37 female. We compared the results of the measurements of both sides of the skull as well as between genders. The measurements were made in millimeters by a digital caliper. Transilumination of the skull with LASER or LEDwas used to assess the correspondence of the digastric point in the inner surface of the skull. The mean age of the skulls was 34,93 years (sd 13,16). The mean distance between the digastric and jugular points were smaller in female skulls in both sides. The mean distance between the digastric point and the sulcus of the sigmoid sinus in 254 measurements was 3,10mm (sd 3,11). The digastric point was over the sulcus of the sigmoid sinus in 49,6% of the cases in the right side and in 29,9% of the cases in the left. The distance between the jugular point and the stylomastoid foramen was smaller in the right side (M 8,89 mm, sd 2,61 mm, p 0,041). Comparing both sexes regardless the side, the distance between the digastric and jugular points and jugular point to the stylomastoid foramen were smaller in female skulls (p 0,000 and 0,006,respectively). The objectives of this work were to validate the digastric point as an useful landmark for suboccipital approaches and its extensions and to compare the measurements in both sexes and between the sides of the skulls.